2013
DOI: 10.1074/jbc.m112.444372
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cortical GABAA Receptor Composition, Physiology, and Endocytosis in a Mouse Model of a Human Genetic Absence Epilepsy Syndrome

Abstract: Background: Heterozygous GABRA1 deletion causes absence epilepsy. Results: The deletion modestly decreased cortical GABA A receptor number but also reduced the rate of receptor endocytosis and thus partially compensated for the deletion by increasing the expression of different receptor isoforms. Conclusion: Heterozygous GABRA1 deletion caused novel alterations in cortical GABA A receptor expression and physiology. Significance: These findings reveal mechanisms of cortical disinhibition in absence epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 74 publications
7
69
2
2
Order By: Relevance
“…Mutations in specific subunits of the pentameric GABA A receptor have been found in probands of human pedigrees with absence epilepsy, and mice haploinsufficient for GABRA1, the GABA A receptor a 1 subunit, successfully recapitulated the human absence phenotype (Arain et al, 2012). Further investigation of this model found that Layer 6 pyramidal neurons are disinhibited but partially compensate by remodeling the channel with kinetically slower subunits (Zhou et al, 2013;Fig. 1).…”
Section: Gaba a Receptor Mutations: Fast Synaptic Disinhibitionmentioning
confidence: 98%
“…Mutations in specific subunits of the pentameric GABA A receptor have been found in probands of human pedigrees with absence epilepsy, and mice haploinsufficient for GABRA1, the GABA A receptor a 1 subunit, successfully recapitulated the human absence phenotype (Arain et al, 2012). Further investigation of this model found that Layer 6 pyramidal neurons are disinhibited but partially compensate by remodeling the channel with kinetically slower subunits (Zhou et al, 2013;Fig. 1).…”
Section: Gaba a Receptor Mutations: Fast Synaptic Disinhibitionmentioning
confidence: 98%
“…Prolonged GABA A a1 deficiency can cause the proliferation of immature filopodial-like dendritic spine protrusions, and a loss of mature dendritic spines, the primary sites of excitatory synapses in the brain (Heinen et al, 2003). Prior studies concerning the effects of cortical GABA A a1 deficiency have largely utilized mice with unconditional heterozygous deletion of Gabra1 or forebrain-selective knockdown with early-life onset (eg, Kralic et al, (2002);Sonner et al, (2005); Zhou et al, (2013)). Instead, we knocked down GABA A a1 selectively in the cortex of mature mice.…”
Section: Discussionmentioning
confidence: 99%
“…Synaptic marker expression was reduced as early as 2 weeks following viral vector delivery, and in the absence of compensatory upregulation of GABA A a2 or GABA A a3. By contrast, GABA A a3 is upregulated following heterozygous deletion (Zhou et al, 2013). Mice with oPFC-targeted GABA A a1 knockdown were unable to select actions based on their consequences, developing instead habit-like behavioral inflexibility, recapitulating the effects of early-life cocaine exposure (Hinton et al, 2014) and chronic stressor exposure (Dias-Ferreira et al, 2009), among other manipulations modeling chronic psychiatric illness in rodents (reviewed by Schwabe et al, (2011);Schwabe and Wolf, (2013)).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations of GABA A receptors are associated with generalized epilepsy [91]. The GABA A receptor antibodies disrupt the GABA A receptor anchoring protein and reduce GABA A receptor inhibition in lengthy seizures, which lead to status epilepticus [92].…”
Section: Anti-gaba Receptor Encephalitismentioning
confidence: 99%